THEOPRENEURICAL LEADERSHIP - Sudibyo, Kusman (Journal of Accounting and Management Innovation, 2019)
ABSTRACT Early Christians made the marketplace the focal point of their ministry because their occupations regularly took them there.Marketplace people played a vital role in the emergence, establishment and expansion of the early church.This was possible because they saw the marketplace as their parish and their business as a pulpit.Christian businessman or Theopreneur generally lives in dual world , in church as congregation and market place as his working place.The output generated is wealth or blessing which undoubtedly provided by God who gives the power to get wealth.Theopreneurical Leadership,  the blending of theology, entrepreneurship and leadership with biblical truth to  unfold the secret for  Theopreneurs on how to utilize their talents to exercise the resources from God  as a steward and not an owner to bless people and fulfill God’s plan for their lives through business .Successful Christian businessman have the opportunity to influence the lives of many people:employees, suppliers, business associates, family and friends, community leaders, governmental officials, and others.This will give significant impact upon the laws, policies and proceedures in our communities KEYWORD :THEOPRENEURICAL LEADERSHIP, THEOPRENEUR